Carcinoid Tumor of the Lung: Hospital-Based Descriptive Study - Ravindrachari Mulukoju; Ganga Ravindra Adimulam; Sneha Leo; Pratap Upadhya; Pampa Chakravarthy Toi (Jurnal Respirasi, 2023)
Introduction: Bronchial carcinoids are slow-growing tumors that are usually asymptomatic until the later stages and mimic most benign conditions clinically. This study presented pulmonary carcinoids (PCs) in terms of diagnosis and management in a tertiary care center. Case: The mean age of presentation was 42.5 years old. Right lung involvement was more common, and the frequency was higher in men. In all patients, second to fourth generations of airways were the site of involvement. The most common symptom was a dry cough. Bronchoscopic biopsy complemented by immune histochemistry was the main diagnostic modality. The majority of patients (60%) had a typical PC. Stage I or III of the disease was the most common presentation. Nine lobectomies and two pneumonectomies were performed on 11 of 15 patients. These patients are performing well to date. Four patients were given only chemotherapy, of which one has survived. The longest follow-up period was 26 months. Conclusion: A high degree of clinical suspicion and familiarity with carcinoids is essential for early identification and a positive clinical outcome, especially in typical carcinoids (TC), as there are no obvious risk factors and various clinico-radiological presentations. In this study of 15 cases, most of the PCs were right-sided and more common in males. The use of a biopsy, either by a guided bronchoscopy or by computed tomography (CT), was confirmatory, and surgical removal was the treatment of choice. Medical therapy may be considered for select patients with carcinoid syndrome or terminal disease.